Sistem Akuntansi Persediaan Barang Dinas Ketenagakerjaan Dan Transmigrasi Daerah Istimewa Yogyakarta - Buffon, Justino; Astuti, Tutut Dewi (Jurnal Ilmiah Wahana Pendidikan, 2023)
The main objective of this study was to find out the inventory recording system at the Yogyakarta Employment and Transmigration Office. The population in this study are all systems in the DIY Department of Employment and Transmigration. The variable observed by the authors in this report is the DIY Inventory Accounting System for the Department of Employment and Transmigration. Based on the research, it was found that the government inventory accounting records used at the Yogyakarta Employment and Transmigration Office used the periodic method. The periodic recording system is a recording system that is only carried out when there is an addition to inventory and does not immediately update the inventory value when usage occurs. The amount of ending inventory is known by carrying out a physical count (stock taking) at the end of the period so that at the end of this period an adjusting entry is made to update the value of the inventory.